The Effect of Applying PQ4R Strategy with a Scientific Approach on Mathematical Problem Solving Ability - Emy Artuti (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine the effect of applying the PQ4R strategy with a scientific approach to the ability to solve mathematical problems in social arithmetic material. Methodology: This research method is quantitative. The research that will be used is true experimental research. In this study, there were 2 sample class groups, namely the experimental and control classes. The author will provide learning treatment using the PQ4R learning strategy with a scientific approach to the experimental class, while the control class, it remains with the usual expository strategy. Main Findings: Based on the results of student activity research, it was obtained that 80% of students were active from the total number of students. Then the assessment results of student activity observation sheets are included in the